2021
DOI: 10.1002/nbm.4516
|View full text |Cite
|
Sign up to set email alerts
|

Imaging acute effects of bevacizumab on tumor vascular kinetics in a preclinical orthotopic model of U251 glioma

Abstract: The effect of a human vascular endothelial growth factor antibody on the vasculature of human tumor grown in rat brain was studied. Using dynamic contrast‐enhanced magnetic resonance imaging, the effects of intravenous bevacizumab (Avastin; 10 mg/kg) were examined before and at postadministration times of 1, 2, 4, 8, 12 and 24 h (N = 26; 4–5 per time point) in a rat model of orthotopic, U251 glioblastoma (GBM). The commonly estimated vascular parameters for an MR contrast agent were: (i) plasma distribution vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…The MRI features of the U-251N animal model tumors correlate with human GBM, including a necrotic center, poorly demarcated, infiltrative tumor borders, and an enhanced rim on T2-weighted imaging (one of the main components of the Dual Gradient Echo used in this study); on post-contrast T1-weighted images an intense rim is observed similar to human GBM 126 . It has already been shown that in murine models, DCE-MRI measures of vascular permeability 59 , 60 , 63 , 64 , 70 , 77 , 82 , 94 , 96 99 , 123 , 129 , 143 148 agree with those of human studies 77 .…”
Section: Discussionmentioning
confidence: 63%
“…The MRI features of the U-251N animal model tumors correlate with human GBM, including a necrotic center, poorly demarcated, infiltrative tumor borders, and an enhanced rim on T2-weighted imaging (one of the main components of the Dual Gradient Echo used in this study); on post-contrast T1-weighted images an intense rim is observed similar to human GBM 126 . It has already been shown that in murine models, DCE-MRI measures of vascular permeability 59 , 60 , 63 , 64 , 70 , 77 , 82 , 94 , 96 99 , 123 , 129 , 143 148 agree with those of human studies 77 .…”
Section: Discussionmentioning
confidence: 63%
“…administration of ketamine (100 mg/kg) and xylazine (10 mg/kg), the tumor volume was measured, and 250 μl whole blood were collected. 29 …”
Section: Methodsmentioning
confidence: 99%
“…administration of ketamine (100 mg/kg) and xylazine (10 mg/kg), the tumor volume was measured, and 250 μl whole blood were collected. 29 F I G U R E 1 TAZ expression was high in the brain tissue of glioma patients, and it was higher in stage III-IV patients than in stage I-II patients. (A) Healthy brain tissue and glioma tissue were sectioned using a pathological section machine, embedded, and fixed.…”
Section: Using a Hamilton Syringe Exosome Suspension Or Pbs Vehicle Wasmentioning
confidence: 97%
“…In these subfigures, the differences among Since the physiological properties of brain tissue are mostly constant across species and pathologies [122][123][124] , the associations of radiomics information with brain tissue physiology revealed in this study, can be expected to reliably scale and translate to human Glioblastoma (GBM). Physiological and mechanical properties of tumor have been shown to characterize heterogeneity in gene expression, and phenotype for Glioblastoma (GBM) 47,53,55,64,71,[125][126][127][128][129][130][131] . Many studies [31][32][33][34][35][36][37][38][39][40][41][42][132][133][134][135][136][137] Zhang et al 41,137 have recently shown the association between the subregional PK-based radiomics information of breast tumor and its histological characteristics.…”
Section: Subfigures 4b-f and 4h-l Clearly Demonstrate How Different T...mentioning
confidence: 99%